Livestock feed and forage options: Briefing meeting with national partners - Mekonnen, Kindu; Getnet, Million; Abdulkadir, Birhan (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Feed is one of the three pillars (feed, breed and health) that influence livestock productivity